Successful pregnancies in post-kidney transplant couples: four case reports - Huang, Hao; Liu, Xinyu; Lin, Xiaoli; Wu, Xiaoying; Qiu, Yingyin; Huang, Hongfeng (Frontiers in Immunology, 2023)
Background The fertility of female kidney transplant recipients is increasing with the progression of transplant management. This article aims to evaluate the clinical prognosis of mothers and newborns for post-kidney transplant couples. Methods From January 2019 to April 2022, a total of four couples, all kidney transplant recipients, were successfully prepared for pregnancy after a rigorous preconception evaluation, including three cases of natural conception and one case of in vitro fertilization. Data regarding the mother and newborn, including general clinical condition and laboratory results, were recorded and assessed throughout the pregnancy and up until 12 months after delivery. Results The mean conception age of the mothers was 34.8 years (30–38 years), and the mean interval between renal transplantation and pregnancy was 6.6 years (3.7–8.7 years). All deliveries were by cesarean section and took place without incident. There were three premature births (<37 weeks; average 35.1 weeks). In case 1 (in vitro fertilization), pre-eclampsia occurred during maternity, and this was the only case in which the fetal weight was less than 2,500 g (average 2,576.7 g). The mean Apgar score (1 min) was 7.8 (6–9) and reached 9 in all cases at 5 min. The mothers’ eGFR rose during mid-gestation, decreased in late pregnancy, and was largely restored along with proteinuria 1 year postpartum. Postnatal evaluation at 6 months showed normal neurological development. In addition, NK cell and IFN-γ levels increased and Treg cell and IL-10 levels decreased along with the onset of pre-eclampsia. Conclusions Pregnancies can succeed in couples who are both kidney transplant recipients. However, there might be higher risks of infertility, prematurity, and low birth weight.